Breach and Attack Simulation Frameworks for Continuous Validation of Enterprise Security Controls - Adetomiwa A. Dosunmu; Peter Olusoji Ogundele (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Modern enterprise environments are increasingly exposed to sophisticated, persistent, and adaptive cyber threats that exploit technical vulnerabilities, misconfigurations, human weaknesses, and process failures. Traditional security validation approaches, such as periodic penetration testing, compliance audits, and vulnerability scanning, are insufficient for assessing real-world security posture in dynamic, cloud-based, and hybrid infrastructures. In response, breach and attack simulation (BAS) frameworks have emerged as a proactive and continuous approach for evaluating the effectiveness of security controls by emulating adversarial tactics, techniques, and procedures across enterprise environments. This paper provides a comprehensive review and conceptual analysis of breach and attack simulation frameworks as a mechanism for continuous security validation. Drawing exclusively on literature and industry developments, the study examines the evolution of BAS, its theoretical foundations, architectural components, simulation methodologies, integration with security operations, and its role in risk-informed decision making. The paper synthesises advances in automated attack emulation, control validation, metrics-driven assessment, and cyber resilience measurement, while highlighting challenges related to realism, scalability, false assurance, and organisational adoption. The study contributes a structured understanding of BAS frameworks and positions them as a critical capability for modern, continuously adaptive enterprise security programmes.